Unidirectional edge modes launched by surface fluctuation in magnetic metamaterials. (29th January 2018) - Chen, Huajin; Luo, Youzhu; Liang, Chenghua; Li, Zhenglin; Liu, Shiyang; Lin, Zhifang
Abstract: We demonstrate theoretically that the surface fluctuation can be used to launch the unidirectional electromagnetic edge mode for a Gaussian beam incident normal to the magnetic metamaterials (MMs) composed of an array of ferrite rods with the uppermost layer introduced position or size fluctuation in the coupling region. Such an edge mode is solely allowed to propagate in one direction due to the time-reversal symmetry breaking in MMs under the exertion of an external magnetic field, and it is substantially enhanced by the magnetic surface plasmon resonance. The nonreciprocal excitation of the edge states can also be understood by examining the scattering amplitudes of different partial waves, which indicate that the 1st order of the angular momentum channel plays a crucial role in realizing the nonreciprocity. The present research might be significant for the implementation of unidirectional absorption and the reexamination of bound states in the continuum in the context of MMs. In addition, the unique optical property can be exploited to design electromagnetic waveguide devices, such as one-way waveguide and wave bender, which are strongly robust against the obstacles placed in the channel of designed devices, facilitating to realize optical integrated circuits.